ECRM Strategy In Improving Services And Sales Of Electronic Products - Qevin Dwi Rafitrah; Dewi Anggraeni; Ruri Ashari Dalimunthe (Jurnal Sistem Cerdas, 2026)
Business competition in the era of globalization demands companies to continuously adapt, one of which is through the implementation of Electronic Customer Relationship Management (E-CRM). Mega Cell Sei Piring Pulau Rakyat, a retail store for electronic products, faces challenges in the form of inconsistent sales fluctuations and customer management that is still manual. If this unstable sales pattern continues without improvement, it has the potential to disrupt profitability and create a risk of loss. This study aims to implement an E-CRM strategy as a strategic solution to improve customer service, optimize sales management, and maintain the company's revenue stability. This qualitative research produces a design and prototype of a web-based E-CRM system (PHP and MySQL) that enables transaction recording, product management, promotion management, and integrated sales reporting. The E-CRM system that has been built facilitates market segmentation and better customer interaction, thus it is expected to improve operational efficiency, reach a wider market through online information access, and encourage customer attraction and loyalty through data-based promotional offers